Malnutrition and infant and young child feeding in informal settlements in Mumbai, India: findings from a census. Issue 3 (3rd March 2015) - Bentley, Abigail; Das, Sushmita; Alcock, Glyn; Shah More, Neena; Pantvaidya, Shanti; Osrin, David
Abstract Childhood malnutrition remains common in India. We visited families in 40 urban informal settlement areas in Mumbai to document stunting, wasting, and overweight in children under five, and to examine infant and young child feeding (IYCF) in children under 2 years. We administered questions on eight core WHO IYCF indicators and on sugary and savory snack foods, and measured weight and height of children under five. Stunting was seen in 45% of 7450 children, rising from 15% in the first year to 56% in the fifth. About 16% of children were wasted and 4% overweight. 46% of infants were breastfed within the first hour, 63% were described as exclusively breastfed under 6 months, and breastfeeding continued for 12 months in 74%. The indicator for introduction of solids was met for 41% of infants. Only 13% of children satisfied the indicator for minimum dietary diversity, 43% achieved minimum meal frequency, and 5% had a minimally acceptable diet. About 63% of infants had had sugary snacks in the preceding 24 h, rising to 78% in the second year. Fried and salted snack foods had been eaten by 34% of infants and 66% of children under two. Stunting and wasting remain unacceptably common in informal settlements in Mumbai, and IYCF appears problematic, particularly in terms of dietary diversity. The ubiquity of sugary, fried, and salted snack foods is a serious concern: substantial consumption begins in infancy and exceeds that of all other food groups except grains, roots, and tubers.